Preservation of health problems in workers servicing railway tunnels of Eastern Siberia - G. V. Kurenkova (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The analysis of the results of medical examinations of workers in Baikal and North-Muya Tunnels East-Siberian Railway. Health studied groups rated as unsatisfactory, which is associated with an the influence of unfavorable factors of production complex: high humidity and air mobility, low positive air temperatures, the lack of natural light, noise and vibration, chemicals, dust, severity of the labor process, hypogeomagnetic field, radon. The number of healthy individuals is insignificant. It is established that the structure of the accumulated incidence among workers of two tunnels significant differences were found. In both groups, registered respiratory disease with prevalence of chronic bronchitis, infectious and parasitic diseases represented mainly fungal infections of nails and feet, and diseases of the eye (more than half of the cases - violation of refraction and accommodation). It is shown that a greater number of cases of respiratory disease in a group of workers of the North Muya tunnel due to the higher (2.5 times) volume activity of radon in the air of the working area, and the availability of sites with high (greater than 2) attenuation geomagnetic field. Defective light climate can cause changes not only in the functional condition of individual organs and systems, but also adversely affects the visual analyzer. The presence of drainage water and humidity favor the spread of fungal diseases of the skin and its appendages. In the preservation of health workers serving the railway tunnels, it is necessary to focus on the regular medical examinations for early detection, treatment, and prevention of diseases, as well as individual and group recreation workers who are exposed to adverse health effects of production factors. Substantiated basic preventative health maintenance workers of railway tunnels through individual sanitation and health preventive measures, avoiding harmful habits, rationalization of supply, the maintenance of the physiological antioxidant and immune-system reactions.